Bootstrapping classical spinning Compton amplitudes with colour-kinematics - Ingrid Vazquez-Holm; Andres Luna (Journal of High Energy Physics)
Abstract We set up a procedure to systematically obtain Compton-like amplitudes in an arbitrary-spin theory, exploiting their factorization properties, and colour-kinematics duality. We furthermore investigate the constraining of Wilson coefficients for arbitrary spinning bodies and its relation to colour-kinematic duality.